"Prion‐Like" Templated Misfolding in Tauopathies. (16th April 2013) - Clavaguera, Florence; Lavenir, Isabelle; Falcon, Ben; Frank, Stephan; Goedert, Michel; Tolnay, Markus
Abstract The soluble microtubule‐associated protein tau forms hyperphosphorylated, insoluble and filamentous inclusions in a number of neurodegenerative diseases referred to as "tauopathies." In Alzheimer's disease, tau pathology develops in a stereotypical manner, with the first lesions appearing in the locus coeruleus and entorhinal cortex, from where they appear to spread to the hippocampus and neocortex. Propagation of tau pathology is also a characteristic of argyrophilic grain disease, where the tau lesions spread throughout the limbic system. Significantly, isoform composition and morphology of tau filaments can differ between tauopathies, suggesting the existence of distinct tau strains. Extensive experimental findings indicate that prion‐like mechanisms underly the pathogenesis of tauopathies.